Obesidade e nível de atividade física em universitários de Região de Fronteira - Pinto, Fernando Ferro (2021)
Over the last few decades, obesity has been increasing worldwide, affecting individuals of all ages, leading to clinical complications and even death. Obesity has become one of the diseases of greatest concern in public health, as it affects individuals both physiologically and psychologically. In view of the risks that obesity can entail, it is necessary to understand whether there are differences in the percentage of obese individuals in the border region and the level of physical activity practice among university students. OBJECTIVE: To analyze the percentage of obese individuals and the level of physical activity practice among university students in the border region. METHOD: Quantitative and cross-sectional study, in which university students from the border region of the city of Foz do Iguaçu-PR, through a link, answered an online questionnaire. The survey was conducted seeking data on the body mass index to diagnose obesity, where the international physical activity questionnaire, short version, which assessed the level of physical activity, was applied. RESULTS: With regard to the level of physical activity of the students in this study, similar results are presented for the Active and Very Active categories, 25% and 31.3% respectively, and for the Body Mass Index (BMI), 48.1 % were considered to have a normal BMI, which is considered a positive result. The result obtained that stands out is the relationship between the level of physical activity and the BMI. The Normal BMI index was 55.8% for Very Active, 44.6% for Active, 46.9% for Active A, 52.5% for Active B and 31.6% for Sedentary. The Obesity index was 9.6% for Very Active, 13.8% for Active, 25% for Active A, 17.5% for Active B and 42.1% for Sedentary. Highlighting mainly the two extremes of the result, where the Normal BMI index was 55.8% for the Very Active category, whereas when observed obesity only 9.6% for very active and the high index of 42.1% for sedentary . In short, we consider that university students classified as Very Active have a normal BMI, whereas most sedentary students are classified as obese. CONCLUSION: Based on the results, it is possible to infer that the percentage of obese individuals in the border region who responded to the questionnaire is lower than in similar studies. This may have occurred due to the approach due to the pandemic- online form – self-report and/or is actually a characteristic of the population addressed. New tentative approaches must be designed, with greater breadth and if possible in a direct way of collecting data.